Study on the Influence Mechanisms of Reservoir Heterogeneity on Flow Capacity During Fracturing Flooding Development - Haimin Xu; Baolun Niu; Li Huang; Lei Zhang; Yongmao Hao; Zichao Yue (Energies)
Low-permeability reservoirs face significant challenges in pressure transmission during field applications of fracturing flooding development. Influenced by reservoir properties and well spacing, fracturing flooding development in such reservoirs often encounters limited propagation of high-pressure zones, ineffective pressure diffusion during water injection, low producer pressure, and poor response. This study develops a numerical simulation model for fracturing flooding development in low-permeability reservoirs of Shengli Oilfield and investigates flow capacity variations under heterogeneous reservoir conditions. Key findings reveal (1) flow capacity is maximized under low-to-high interwell permeability distribution and minimized under high-to-low distribution, with a five-fold difference between the two patterns; (2) flow capacity exhibits near-linear growth with increasing average permeability, while showing an initial increase followed by decrease with growing permeability contrast, peaking at contrast ratios of 4–6; (3) flow capacity improves with injected volume but demonstrates diminishing returns after reaching 0.05 PV, establishing this value as the critical threshold for optimal fracturing flooding performance.